CIVIL CONSTRUCTION IN NATIONAL SOLID WASTE POLICY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
This paper aims to address the complex issue of the huge generation of solid waste in Brazil, in the area of ​​civil construction. We seek ways and means to have the reduction, reuse and recycling of materials and construction leftovers, in the form of directing waste to build housing for low-income people. With this, the right to housing and urban planning is promoted obliquely, also part of the list of collective rights. It proposes a model of social control to be exercised by organs and people with notorious competence and knowledge in the environmental field (Civil and Environmental Engineering, Law, Management, etc.), in the formation of citizenship nucleus and environmental education, using methodologies, applied to the construction sector, with reduction and reuse models. Members would assume an effective role in environmental citizenship through the implementation of other instruments of the national solid waste policy, such as the shared responsibility for the product life cycle. And when social control through citizenship alone does not have the necessary effects, which may be used in implementing the purposes of the PNRS, the Public Civil Action to be managed by the social control body itself, which presents itself with all the necessary apparatus for this, and this proposal is a form of effective citizenship and environmental participation.